Features of establishment of early lactation in women who gave birth after in vitro fertilization. (13th November 2019) - Samchuk, P; Rozalieva, Y; Gil, A
Abstract: Background: Breastfeeding gives babies the best possible start in life and breastmilk works like a baby's first vaccine. Pregnancy resulting from IVF is often associated with placental insufficiency in which the hormone-producing function of placenta can be compromised that may result in reduced lactogenesis. The aim was to study the emergence of early lactation after IVF in women with a history of infertility. Methods: The study involved 34 women after IVF with a singleton full-term pregnancy with a history of tubal-peritoneal infertility. Control group comprised of 47 women with naturally occurred pregnancy. Delivery occurred naturally. All women were assessed for hormonal function of placenta for a period of 16-18, 28-32, and 37-38 weeks of pregnancy. The average daily amount of milk on a 5th day after delivery was measured. Results: In the IVF group vs. control group there was a decrease in the production of hormones by the placenta (progesterone, estriol, placental lactogen) preparing the mammary glands for lactation (p < 0.05). At gestational age of 16-18 weeks progesterone level in IVF group was 172.2±10.72 nmol/l; 28-32: 274.2±8.45 nmol/l; 37-38 weeks: 343.2±9, 1 nmol/l. The level of estriol at 16-18 weeks was 2.87±1.42 ng/ml; 28-32: 10.94±0.6 ng/ml; 37-38 weeks: 25.21±0.22 ng/ml. Placental lactogen at16-18 weeks: 1.15±0.2 nmol/l; 28-32: 6.39±0.69 nmol/l; 37-38 weeks: 7.23±0.59 nmol/l. On day 5 normal lactation was observed in 21(62%) and 43(91.5%) women in IVF and control group, respectively (p < 0.05). Conclusions: Increased number of cases of hypolactation was observed in women after IVF, which was associated with decrease in the hormonal function of placenta. Women who have given birth to children after IVF require special attention from the side of medical personnel and from loved ones in the early stages of establishment of breastfeeding. Key messages: IVF is a risk factor for hypolactation, which is associated with placental hormone-producing insufficiency. Women who have given birth after IVF require support aimed at promotion of early lactation and breastfeeding.